How do you solve #x^2+3x+1=0#?
We can solve this by completing the square ...
So
By signing up, you agree to our Terms of Service and Privacy Policy
To solve the quadratic equation (x^2 + 3x + 1 = 0), you can use the quadratic formula, which states that for an equation of the form (ax^2 + bx + c = 0), the solutions are given by:
[x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{{2a}}]
In this case, (a = 1), (b = 3), and (c = 1). Substituting these values into the formula:
[x = \frac{{-3 \pm \sqrt{{3^2 - 4(1)(1)}}}}{{2(1)}}]
[x = \frac{{-3 \pm \sqrt{{9 - 4}}}}{{2}}]
[x = \frac{{-3 \pm \sqrt{5}}}{{2}}]
So, the solutions are:
[x = \frac{{-3 + \sqrt{5}}}{{2}}] and [x = \frac{{-3 - \sqrt{5}}}{{2}}]
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7